Regulations of Political Opposition between Islamic Political Jurisprudence and Positive Law - chouya, said; mihi, abdelhak (El Omda in Linguistics and Discourse Analysis, 2024)
The abstract : This study contains the political opposition in each of the Islamic political jurisprudence and the statutory laws and regulations that control both of them . As they are considered as people representatives and The careful observer of their interests in front of the governess systems , therefore in order to protect this role , each one of them must commit to the regulations weather the legitimacy for Islam or the legal one for the positivist systems That organize their own job and protect it's identity despite their similarities, they have a lot of different regulations which made each of them have their own special identity , especially with the sources , The temporal and spatial dimension, the working ways and movement methodology and the strategic dimensions.